White matter abnormalities associated with Alzheimer's disease and mild cognitive impairment: a critical review of MRI studies. (May 2013) - Radanovic, Marcia; Pereira, Fabrício Ramos Silvestre; Stella, Florindo; Aprahamian, Ivan; Ferreira, Luiz Kobuti; Forlenza, Orestes Vicente; Busatto, Geraldo F
In this article, the authors aim to present a critical review of recent MRI studies addressing white matter (WM) abnormalities in Alzheimer's disease (AD) and mild cognitive impairment (MCI), by searching PubMed and reviewing MRI studies evaluating subjects with AD or MCI using WM volumetric methods, diffusion tensor imaging and assessment of WM hyperintensities. Studies have found that, compared with healthy controls, AD and MCI samples display WM volumetric reductions and diffusion tensor imaging findings suggestive of reduced WM integrity. These changes affect complex networks relevant to episodic memory and other cognitive processes, including fiber connections that directly link medial temporal structures and the corpus callosum. Abnormalities in cortico–cortical and cortico–subcortical WM interconnections are associated with an increased risk of progression from MCI to dementia. It can be concluded that WM abnormalities are detectable in early stages of AD and MCI. Degeneration of WM networks causes disconnection among neural cells and the degree of such changes is related to cognitive decline.